The Arthropods Diversity in Chili (Capsicum annum L.) Cultivation in Pagaralam, South Sumatra: Arthropods Diversity in Chili (Capsicum annum L.) Cultivation in Pagaralam, South Sumatra - proteksi, Arsi; Gunawan, Bambang; Pratama, Rahmat Pratama; Gustiar, Fitra; Suparman; Hamidson, Harman Hamidson; Pujiastuti, Yulia Pujiastuti; Umayah, Abu Umayah; Tricahyati, Titi Tricahyati; Pradiefta, Muhammad Rafii Pradiefta (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2024)
Red chili (Capsicum annuum L.) is one of important types of vegetables and also has many varieties that have distinctive colors and shapes, chili is also considerd as one of vegetable that has high economic value. Chili is usually consumed in from of fresh, dried and processed as vegetables and also seasonings, in addition to functioning as a food flavor enhancer. Many obstacles faced by farmers in chili cultivation are plant disturbing organisms such as pests and diseases. Some important pests that commonly attack chili plants are fruit flies (Bactrocera spp), armyworms (Spodoptera litura) and aphids (Aphis gossypii). The purpose of this field practice was to determine the diversity of arthropods and the intensity of pest attacks in Pagaralam City on ten chili fields with different ages. This field practice is expected to provide information about arthropod diversity and attack intensity, especially to farmers as the main actors in agriculture. This insect observation method is carried out using the Diagonal sampling method, Scan sampling (Visual observation) and observing the intensity of the attack. The results of the observations obtained are that the chili farmers have carried out the concept of integrated pest management, but they are not aware of it, and the pests obtained in the field are fruit flies (Bactrocera spp), armyworms (Spodoptera litura) and aphids (Aphis gossypii), and for arthropod diversity it varies on each land.